Marketing social corporativo e empreendedorismo social : uma análise da atuação empresarial por meio de fundações e institutos - Mattiello, Kerla (2008)
Corporate social marketing is understood as an effective way of building the mark of a company or of their products and services, to reinforce, to demonstrate and to explicit corporate values, as well as to act socially through corporate investment in the community, visible especially through programs of social actions of long period, associates to the company and his/her mark. Such programs initially were implemented directly by the own companies. In spite of, in the last years a phenomenon of relevant character for the field of the entrepreneurship wakes up the attention: programs of social actions have been more and more developed through institutes and business foundations that are fruits of enterprising actions returned for the creation of new destined organizations her act socially in the third section. The study looked for to evidence the actions of corporate social marketing (MSC) of great companies Brazilian creators of institutes or business foundations through the analysis and description of the programs of MSC and if this practice can influence the initiative of undertaking institutes and business foundations. The method of research of the type survey was used and as instrument of collection of data the questionnaire. The work treats of that phenomenon still unexplored for entrepreneurship researchers and of marketing, whose magnitude can be observed through empiric evidences found in the extent of GIFE - Group Foundation, Institutes and Companies, group chosen as research focus.